2015
DOI: 10.1210/jc.2014-4465
|View full text |Cite
|
Sign up to set email alerts
|

Differential Gene Expression in Diabetic Nephropathy in Individuals With Type 1 Diabetes

Abstract: Together, these data suggest that SF from T1D patients undergo epigenetic modifications resulting in increased expression of genes in healing and repair pathways. These responses, much more robust in patients protected from DN, suggest that epigenetic factors are important in DN risk.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 35 publications
0
12
0
Order By: Relevance
“…Gene expression microarrays have been widely used in diabetic studies, because alterations in transcriptional profiles provide a robust and sensitive way to better understand the mechanisms of the disease and its complications. Microarray analyses have previously been used to investigate the mechanisms underlying diabetic cardiomyopathy [ 24 ], diabetic nephropathy [ 25 ], diabetic bone disease [ 26 ], and diabetic periodontitis [ 27 ] in diabetic patients or animal models. However, only one study has been conducted in patients with diabetic neuropathy to identify the DEGs and the related biological pathways responsible for the progression of diabetic neuropathy [ 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…Gene expression microarrays have been widely used in diabetic studies, because alterations in transcriptional profiles provide a robust and sensitive way to better understand the mechanisms of the disease and its complications. Microarray analyses have previously been used to investigate the mechanisms underlying diabetic cardiomyopathy [ 24 ], diabetic nephropathy [ 25 ], diabetic bone disease [ 26 ], and diabetic periodontitis [ 27 ] in diabetic patients or animal models. However, only one study has been conducted in patients with diabetic neuropathy to identify the DEGs and the related biological pathways responsible for the progression of diabetic neuropathy [ 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…This is further supported by the evidence of higher levels of oxidative stress in RCC patients (Hori et al, 2007;Ganesamoni et al, 2012), in renal injury related to obesity (Quigley et al, 2009), and in an experimental model of renal carcinogenesis (Gago-Dominguez et al, 2002). Increased oxidative stress and activation of oxidative stress-induced DNA damage repair pathway in kidney cells of diabetic patients have been reported (Forbes et al, 2008;Kashihara et al, 2010;Caramori et al, 2015). Additionally, several chemotherapeutic agents, including doxorubicin itself, also generate ROS and thereby increase the oxidative stress burden (Ferlini et al, 1999;Pervaiz and Clement, 2004;Sullivan and Graham, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…Earlier, a study in DN was published that has utilized transcriptome profiling of fibroblasts from 100 type 1 diabetes patients from the longstanding Genetics of Kidneys in Diabetes cohort. It has suggested that patients who were protected from DN might undergo more robust epigenetic modifications resulting in enriched expression of genes involved in cell healing and repair pathways, and that epigenetic factors play a role in DN risk 77 .…”
Section: Studies Regarding Epigenetic Factors In Human Diabetic Nephrmentioning
confidence: 99%